2021
DOI: 10.1182/blood-2021-151550
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells of Acute Myeloid Leukemia Patients Exhibit Exhausted Phenotype with Impaired Functional Activity

Abstract: Acute myeloid leukemia (AML) accounts for about one third of all leukemias, with half of all leukemia deaths. The low 5-year survival rate and manifestation of this deadly disease in old age reinforce the need for new safe and effective AML therapies. Considering the exceptional role of immune cells in the recognition and elimination of tumor cells, one of these methods is immunotherapy. However, for the development of immunotherapeutic approaches, it is necessary to clearly understand the role of certain effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Clinical studies observed a significant reduction in the number of NK cells in AML patients compared to normal values and the frequency of NK cells was inversely proportionate with prognosis and OS [ 90 , 91 ]. Furthermore, studies found that NK cells of AML patients have a significantly lower capacity to secrete IFNγ and showed numerous signs of an exhausted phenotype, as compared to healthy controls [ 92 , 93 ]. These include underexpression of activating receptors such as NKG2D, DNAM-1 and NKp30 as well as overexpression of inhibitory receptors such as NKG2A and KIR2DL1 [ 93 , 94 ].…”
Section: The Innate Immune System In the Tumor Microenvironment Of Amlmentioning
confidence: 99%
“…Clinical studies observed a significant reduction in the number of NK cells in AML patients compared to normal values and the frequency of NK cells was inversely proportionate with prognosis and OS [ 90 , 91 ]. Furthermore, studies found that NK cells of AML patients have a significantly lower capacity to secrete IFNγ and showed numerous signs of an exhausted phenotype, as compared to healthy controls [ 92 , 93 ]. These include underexpression of activating receptors such as NKG2D, DNAM-1 and NKp30 as well as overexpression of inhibitory receptors such as NKG2A and KIR2DL1 [ 93 , 94 ].…”
Section: The Innate Immune System In the Tumor Microenvironment Of Amlmentioning
confidence: 99%